Aurora Leadership Institutes: Assisting future leaders to maximise their leadership skills and potential - Lilley, Spencer C (My University, 2008)
This paper provides background information on the Aurora Leadership Institutes and the Aurora Foundation. The latter part of the paper focuses on the looming leadership crisis in the library profession in New Zealand and overseas and identifies several strategies that require implementation to ensure that the crisis is averted.
Paper presented at Oceans of Opportunities: Library and Information Association of New Zealand Aotearoa 2003 Conference, 7 – 10 October 2003 Napier, New Zealand
Keywords: Leadership; Librarianship; Fields of Research::220000 Social Sciences, Humanities and Arts-General